(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper analyses gender stereotypes in textbooks for Spanish as a foreign language for adolescents and young people, which are used in secondary schools in Serbia. The corpus consists of six manuals published in the 21st century by Spanish publishers with a long tradition in publishing teaching materials for Spanish as L2. Apart from the theoretical framework, in which we will discuss the terms gender and sex, and the importance of school and textbooks in transmitting gender ideology, gender stereotypes will be examined in the texts, photos and illustrations. The results of this qualitative research indicate that, despite the fact that the presence of gender stereotypes in textbooks is reduced to a minimum, they continue to be present. That is due to the patriarchal cultural models of the Spanish society, in which the analyzed textbooks have been created. This may have an impact on the development of gender ideology and the construction of gender identity among adolescents and young people who use analyzed manuals in the context of their own culture.